Spermatogenic Inhibition Properties of a Phenolic Phytoestrogen Isolated from Momordica charantia (Bitter Guard) Seeds - Patil, Sharanabasappa A. (Journal of Pharmacy and Nutrition Sciences, 2023)
Mechanisms and potencies of phytoestrogens are not completely clarified and they may be considered potential endocrine disruptors, and therefore caution should be exercised while taking them. Eating very high levels of some phytoestrogens may pose some health risks. Reproductive problems have been documented in laboratory animals, farm animals and wildlife that ate very high (up to 100% of their diet) amounts of phytoestrogen-rich plants. Sheep consuming large amounts of clover showed infertility and reproductive disorders. Cheetahs in captivity also had reduced fertility rates when consuming a feline diet composed of a soybean product, which was reversed when it was removed from the diet. Toxicities associated with herbal medicines that include phytoestrogens have also been reported in the literature. Phenolphthalein a phenolic phytoestrogen has been isolated from the crude ethanol extract of Momordica charantia Linn. seeds. After preparative HPLC whitish amorphous compound was obtained. Its structural elucidation using IR, NMR and Mass spectral data revealed that the molecule isolated from the ethanol extract of M. charantia seeds was surprisingly, phenolphthalein. In order to clarify testicular influence of ethanol extract, fractions and isolated phenolphthalein were treated for sixty days to adult male albino rats. All the treated groups showed statistically significant reduction in testis weight. On histological examinations of testis showed spermatogenic inhibition effect, as the number of spermatogonia, spermatocytes, spermatids and spermatozoa were significantly decreased.